Work–family conflict among Australian dual-earner couples: testing the effects of role salience crossover and gender. Issue 10 (31st May 2019) - Abeysekera, Lakmal; Gahan, Peter
Abstract: Drawing on identity theory, this study examined the extent to which the salience (i.e. importance) individuals in dual-earner couples attached to their respective work and family roles determined their partner's experience of work-to-family (W-F) and family-to-work (F-W) conflict through crossover effects. Using matched surveys, data were collected from a sample of 94 Australian dual-earner couples. Consistent with our predictions, results supported couple-level crossover effects of role salience to influence each partner's experience of W-F and F-W conflicts. In addition, the impact of crossover effects on W-F and F-W conflicts was found to be more pronounced for women than men. Implications for theory and practice are discussed.